1978
DOI: 10.1128/iai.19.2.553-561.1978
|View full text |Cite
|
Sign up to set email alerts
|

Impaired chemotactic responsiveness of macrophages from gnotobiotic rats

Abstract: Peptone-induced macrophages obtained from gnotobiotic (GB) rats responded poorly to chemotactic stimuli that have a powerful, attractive influence upon the cells of conventional donors. Monocyte recruitment from the circulation into peptone-induced exudates also was impaired in GB subjects. Although relatively more resident cells are present in exudates borne by GB donors, their number cannot in itself account for the sluggish response of peptone-induced cells from GB rats. Neutrophil accumulation in the infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…23:286, 1964). There is some evidence that changes in macrophage behavior are responsible for this impairment (14), although the studies do not indicate whether the changes are macrophage mediated only or whether disturbed lymphocyte-macrophage interactions are involved. Our findings have demonstrated that several properties of GF macrophages are different from the corresponding properties of CONV macrophages, indicating some dysfunction of GF macrophages.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…23:286, 1964). There is some evidence that changes in macrophage behavior are responsible for this impairment (14), although the studies do not indicate whether the changes are macrophage mediated only or whether disturbed lymphocyte-macrophage interactions are involved. Our findings have demonstrated that several properties of GF macrophages are different from the corresponding properties of CONV macrophages, indicating some dysfunction of GF macrophages.…”
Section: Discussionmentioning
confidence: 93%
“…GF animals are able to synthesize immunoglobulins (12, 34), and their rejection of skin allografts is similar to that of CONV animals (32). Generation of lymphocyte-dependent, antigeninduced monocyte chemotactic activity is also normal in GF animals (14). However, GF animals are less resistant to tubercle bacilli and other infectious agents that provoke a vigorous cell-mediated immune response in CONV subjects (35; E. M. Lerner, Fed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings thus suggest that suppressor T cells may be more dominant in the CV state than in the GF state of these lowresponder F344 rats. It seems that a bacterial flora may modulate the development of the immune apparatus such as T-helper, T-suppressor, or B-cells or macrophages (4), which is under genetic control.…”
Section: Nd Nd Ndmentioning
confidence: 99%
“…We have demonstrated that germfree mice (nude and euthymic) are also resistant to disseminated, as well as mucocutaneous, candidosis (12,13). Because many functional activities of macrophages from germfree mice are impaired (7,8,17), we proposed that normally functioning macrophages might, in fact, be involved in the pathogenesis of disseminated Candida infections.…”
mentioning
confidence: 99%